Promoting child development and mental health in adult psychiatric care : a nurses' perspective - Korhonen, Teija (Publications of the University of Eastern Finland, ISSN 1798-5706, 2010)
Abstract.
Keywords: Parenting; Questionnaires; Mentally Ill Persons; Professional-Family Relations; Child Welfare; Family Health; Nurses; Mental Health; Child of Impaired Parents : psychology; Mental Disorders : psychology; Parents : psychology; Patient-Centered Care; Family Nursing; Psychiatric Nursing; Social Support; Parent-Child Relations; Child of Impaired Parents; Mental Disorders; Parents; Attitude of Health Personnel; perheet; psykiatrinen hoito; vanhemmuus; lapsilähtöisyys; perhetyö; ehkäisevä mielenterveystyö; mielenterveys; lapsen kehitys; lapset (ikäryhmät); sairaanhoitajat; mielenterveysongelmat; vanhemmat; psyykkisesti sairaat; psykiatriset potilaat; mielenterveyshoitajat; hoitotyö; perhehoitotyö; tukeminen; sosiaalinen tuki; familjer; psykiatrisk vård; föräldraskap; barnperspektiv; familjearbete; förebyggande mentalhygien; mental hälsa; barnets utveckling; barn (åldersgrupper); sjukskötare; psykiska problem; föräldrar; psykiskt sjuka; psykiatriska patienter; mentalvårdare; familjevårdsarbete; vårdarbete; stödjande; socialt stöd; psykiatrinen hoitotyö; children